Resilience of rural women vendors in Bihar, India - Veettil, Prakashan Chellattan; Gupta, Ishika; Choudhury, Samira (International Rice Research Institute, 2023)
Resilient supply chains are at the backbone of any well-functioning market. This paper examines how resilient the supply chains are for female vendors and what are the types of challenges they face when selling their products. A survey of both traditional markets and small village retail shops was conducted in 50 clusters in Nalanda district of Bihar, India. A census was carried out of all markets and retail shops within a cluster. For the survey, the market vendors and retail shops identified in the census were further stratified into different categories as per the products they sold. Even with this inclusive approach of sampling, we found only 27% female in retail shops and less than 5% as market vendors. Wholesalers were the primary supplier for both female and male vendors and retail shop owners and the female owners were located closer to their respective suppliers. When choosing a supplier, female vendors took into consideration whether a credit facility was available or not, whereas male vendors and shop owners considered the quality of the product to be most important. One of the biggest challenges that female vendors face while selling their products was that there were not enough customers, whereas male vendors faced competition from their peers. Male retailer shop owners mentioned price fluctuations as their biggest challenge whereas their female counterparts mentioned low profit margins as a challenge. In summary, we observed low women participation in organized markets but relatively higher for retail shops.